Opt-out HIV testing: An ethical analysis of women’s reproductive rights - Fields, Loren (Nursing ethics, 2011)
As the HIV epidemic continues to grow worldwide, women are increasingly and disproportionally affected. With the introduction of anti-retroviral medications that have been found to effectively prevent perinatal transmission of HIV, the approach to HIV testing in pregnant women has grown increasingly more controversial. In recent years, the model of voluntary counseling and testing (VCT) has come into question with opt-out testing now advocated for by the Centers for Disease Control and occurring widely in pregnancy. The benefits of opt-out testing are numerous and may justify its use in replacing the VCT that many have come to see as insufficient. An ethical analysis of opt-out testing suggests it may be at odds with true informed consent and involve a degree of coercion that would not be allowed outside the prenatal setting. If opt-out testing is going to remain the standard of care then the ethical issues it raises must be made transparent. Strategies need to be designed for ensuring that HIV counseling and testing in pregnancy is done in accordance with ethical and reproductive rights principles.